Electrodeposited CdS/CdTe solar cells - Mohamad, Souad A. (IIUM Press, 2011)
The formation steps necessary for producing high quality electrodeposited CdS / CdTe solar cells are described. The key step in this process involves the heat treatment of the as-deposited n-type CdTe layers at around 400 °C. The results of studies made on the structural, electrical and optical properties of the electrodeposited CdS, CdTe films are presented. CdS/CdTe hetero-junction solar cells with reasonable efficiency have been demonstrated using electrodeposition techniques